Short stature, unusual face, delta phalanx, and abnormal vertebrae and ribs in a girl born to half‐siblings. Issue 5 (31st March 2017) - Pogue, Robert; Marques, Felipe A.; Kopacek, Cristiane; Rosa, Rosana C. M.; Dorfman, Luiza E.; Mazzeu, Juliana F.; Flores, José A. M.; Zen, Paulo R. G.; Rosa, Rafael F. M.
Abstract : Delta phalanx is a rare abnormality typically associated with additional features. We describe a patient with a phenotype resembling Catel–Manzke syndrome, but with delta phalanx and abnormal vertebrae and ribs. The patient was the only child of half siblings born with a marked prenatal growth deficiency. At 10 years of age, she had a short stature, long face, long and tubular nose with small alae nasi, high palate, short and broad thorax, and short index fingers with radial deviation. There were hyperpigmentations following Blaschko's lines. Radiology showed a proximal delta phalanx in the index finger of hands, abnormal vertebrae, and fused and small ribs. GTG‐Banding karyotype and microarray analysis yielded normal results. Exome sequencing identified 25 genes that harbored homozygous variants, but none of these is assumed to be a good candidate to explain (part of) the phenotype. The here described patient may have a new condition, possibly following an autosomal recessive pattern of inheritance, although due to the high degree of consanguinity a compound etiology of the phenotype by variants in various genes may be present as well.